(untitled) (Scripta : English Department Journal, 2026)
Teaching English vocabulary to students with intellectual disabilities remains challenging because they need concrete visual support, repeated exposure, and teacher guidance to understand and remember new words. Picture cards are often used as visual instructional media, but their pedagogical value depends on how teachers implement them in classroom practice. This study aims to explore how picture cards are implemented in teaching English vocabulary to students with intellectual disabilities in a special school context. This research used a qualitative case study design involving one English teacher and one eighth-grade classroom at a special junior high school in North Sumatra, Indonesia. Data were collected through non-participant observation, semi-structured interview, document analysis of two lesson plans, and were analyzed using inductive thematic analysis. The findings reveal that picture cards supported meaning-making, attention building, guided practice, differentiated support, and repeated vocabulary use. The study concludes that picture cards functioned not merely as visual aids, but as flexible pedagogical tools for organizing meaningful, structured, and adaptive vocabulary instruction.